Extending urban energy transitions to the mid-tier: Insights into energy efficiency from the management of HVAC maintenance in 'mid-tier' office buildings. (March 2023) - Daly, Daniel; Carr, Chantel; Daly, Matthew; McGuirk, Pauline; Stanes, Elyse; Santala, Inka
Abstract: Older, smaller and poorer quality commercial buildings (the 'mid-tier') make up much of the commercial building stock and are crucial for urban energy transitions. Action must extend beyond new commercial buildings and high-end building retrofit projects to realise deep decarbonisation of the built environment. Mid-tier buildings offer substantial opportunity for energy retrofits, though the sector lags behind premium office buildings. Comparatively, different ownership structures, tenant profiles, and facilities management regimes challenge the value-proposition for energy transition, and little is known about how to leverage energy performance improvements in this crucial sector. Focussing on the management of heating, ventilation and air-conditioning (HVAC) systems as an entry point for improvement, this paper presents empirical evidence from the largest survey conducted with Australian HVAC contractors, facility managers, and system engineers to date. The results explicate the realities of managing energy in mid-tier office buildings in Australia as a socio-technical undertaking. Our analysis identifies limits and opportunities for shaping energy efficiency of HVAC maintenance, focussed on issues pertaining to workforce, building and systems, and maintenance practices. Further, we draw out policy imperatives needed to address hurdles created by multiple market failures that complicate energy transition in mid-tier buildings.